حجية عموم البلوى عند الاصوليين - الرفاعي، أنس محمود توفيق العواطلي (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنين بالقاهرة, 2016)
نظر الأصوليون إلى حدوث الوقائع والمستجدات حتي تصبح من البلاء العام الذي قد يؤثر على النظر في الأحكام الشرعية، بين مانع ومجيز، ومشترط لبعض الشروط، وهذا البحث: في حجيه عموم البلوى عند الأصوليين يغطي جانبا مهما من التعريف بعموم البلوى وأثرها على الحكم الشرعي وقد بنيته على أربعة فصوول، وخاتمة، ومصادر. الأول: في حقيقة عموم البلوى، والثاني، في أدلة عموم البلوى وشروطه، والثالث، في أسباب عموم البلوى، والرابع في صلة عموم البلوى بأصول الفقه.
The Evidentiary Nature of Widespread Hardship According to Scholars of Legal Theory Prepared By: Dr. Anas Mahmud Tawfiq al-'Awatili al- Rafi'i Shaykh Nuh Ali Qudah Faculty of Shari'ah and Law World Islamic Sciences and Education University Some scholars of legal theory give evidentiary status to new situations that create widespread hardship, some don’t, and some stipulate conditions. This study on the evidentiary status of widespread hardship according to the scholars of legal theory covers the import topics of the definition of "widespread hardship" and its effect on legal rulings. I have organized it into four sections, a conclusion, and a bibliography. Section 1: The Definition of Widespread Need Section 2: The Proofs of Widespread Need Section 3: The Causes of Widespread Need Section 4: The Relation of Widespread Need to Legal Theory
Keywords: الفقة الاسلامى -- اصول الفقه -- العلماء الاصوليين -- الاحكام الشرعية